2016
DOI: 10.1111/php.12652
|View full text |Cite
|
Sign up to set email alerts
|

The Photostabilizing Effect of Grape Seed Extract on Three Common Sunscreen Absorbers

Abstract: The photostabilizing ability of grape seed extract on three common sunscreen absorbers, 2-ethylhexyl-p-methoxycinnamate (EHMC), benzophenone-3 (BP3) and tert-butylmethoxy dibenzoylmethane (BMDBM), was investigated. Samples were exposed to simulated solar radiation and monitored by spectrophotometric and chromatographic methods. The chemical composition of the grape seed extract was determined by GC-MS and HPLC-MS, and the major secondary metabolites were found to be epicatechin and catechin. Exposure of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…It seems that biological protection from UVB light demonstrated for green tea catechins in a number of publications 13 , 15 , 21 could be mainly attributed to their capacity as free radical scavengers and antioxidants. 18 Another, indirect although, confirmation of this assumption was obtained in our experiments with the effects of polyphenols on P65 phosphorylation induced by UVA+UVB exposure ( Fig. 4 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It seems that biological protection from UVB light demonstrated for green tea catechins in a number of publications 13 , 15 , 21 could be mainly attributed to their capacity as free radical scavengers and antioxidants. 18 Another, indirect although, confirmation of this assumption was obtained in our experiments with the effects of polyphenols on P65 phosphorylation induced by UVA+UVB exposure ( Fig. 4 ).…”
Section: Discussionsupporting
confidence: 75%
“…Secondary metabolites such as epicatechin and catechin from grape seeds have been proposed to stabilize common synthetic sunscreens through free radical scavenging mechanism. 18 To phenolics possessing antioxidant and anti-inflammatory properties have been recently attributed anti-photoaging and UV-induced carcinogenesis preventive effects of topical botanics like Polypodium leucotomos extract (Fernblock ® ), 19 propolis, plants, and lichens. 15 …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that there are other factors that may interfere with the final SPF of a sunscreen formulation. Not only the concentration and combination of UV filters are critical, but also the emulsifiers, vehicles and solvents used, the viscosity of the vehicle, active-vehicle, active-skin and vehicle-skin interactions and others [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…BP-4, a soluble UVB filter, can stabilise EGCG to produce effective anti-oxidants. Catechin preparations made with lipid ingredients are less stable in heat, so it is necessary to Gallego et al 2017, Spizzirri et al 2009, Nadim et al 2014, Feng et al 2014, Feng et al 2013, Zhong and Shahidi 2011, Muhammad et al 2014, Li and Seeram 2018, Choi et al 2018, Shoko et al 2018, Lima et al 2016 UV protection Improve the stability of catechins in sunlight and increase the UV protection effect Zhang et al 2016, Yoshino et al 2013, Niu et al 2017, Huang et al 2007, Martincigh and Ollengo 2016, Parisi et al 2012, Kim et al 2012, Xia et al 2005 Anti-microbial activities Demonstrates anti-microbial activity and develops pharmaceuticals and functional cosmetics de Oliveira et al 2017, Aoshima et al 2009, Goyal et al 2017 Anti-allergenic and antiinflammatory activities…”
Section: Discussionmentioning
confidence: 99%
“…Various analyses, including3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and western blot assays, show that ECG is a powerful cure for UVB-induced damage to HaCaT keratinocytes (Huang et al 2007). Exposure to simulated solar radiation with sunscreen sorbents showed that grape seed extracts have broad-spectrum protection due to their high photostability and a red shift over the entire UVA and UVB ray index (Martincigh and Ollengo 2016). Flavonoids show high light and heat stability in the preservation and release of methacrylic acid-grafted poly (N-vinyl-pyrrolidone) acid-grafted (N-vinyl-pyrrolidone) (Parisi et al 2012).…”
Section: Uv Protection Activitymentioning
confidence: 99%